PERBEDAAN PENDAPATAN ASLI DAERAH SEBELUM DAN SESUDAH OTONOMI DAERAH DI KABUPATEN/KOTA DI PROVINSI BALI - Pradnyana, Gde Adi; Erawati, Made Adi (E-Jurnal Akuntansi, 2016)
The purpose of this study was to analyze and get the empirical evidence difference Local Revenue (PAD) before and after decentralization at district / city in the province of Bali. Determination of the saturated sample using sampling techniques and observation period of 5 years. This study using paired t-test. The results showed revenue (PAD) before the Regional autonomy is different from the original income (PAD) after regional autonomy throughout the County and City in the province of Bali. PAD in the county and city in the province of Bali has increased, this is due to the local revenue that was originally used in conjunction with the central government, now managed independently by local authorities, it is supported also by the existence of the province of Bali as a tourist area that has a high potential to contribute to PAD.
Keywords: Acceptance PAD Regency/City Regional Autonomy